Morphometric differentiation of five biotypes of Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae: Aphidiinae) in Iran - Barahoei, Hossein; Madjdzadeh, Seyed Massoud; Mehrparvar, Mohsen (Zootaxa, 2011)
Morphometric analyses were carried out on five biotypes of Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae: Aphidiinae) associated with five host aphid species, Aphis craccivora Koch, Aphis fabae Scopoli, Aphis gossypii Glover, Brachyunguis zygophylli (Nevsky) and Melanaphis sacchari (Zehntner). Sixteen morphological characters were measured on female specimens of L. fabarum. Two multivariate discriminant analyses, discriminant function analysis and Unweighted Pair Group Method with Arithmetic mean cluster analysis, were employed to discriminate among L. fabarum biotypes on a morphological basis. Both discriminant function analysis and cluster analysis revealed significant morphological differences. Specimens of L. fabarum reared on Melanaphis sacchari/ Sorghum halepense association showed clear differentiation from other L. fabarum biotypes. A stepwise discriminant function analysis selected Distance between R1-R2 junction and outer margin of wing, Metacarpus length, Width of first tergit, Basal vein length and Femur length that showed the highest contribution to the separation of host-adapted biotypes. A dendrogram of the cluster analysis based on data of squared Euclidean distances classified biotypes in different groups. This study demonstrates that morphometric analysis of morphological characters can efficiently discriminate among host-associated groups based on size variation and clearly separate biotypes of L. fabarum. We concluded that L. fabarum biotypes are not homogeneous morphological entities, and represent different host-associated forms.